Sawah Surjan Environmental Management for Food Crop Diversification in Kulon Progo of Yogyakarta, Indonesia - Utami, Sri Nuryani Hidayah; Hermania, Pradysta Maya; Purwanto, Benito Heru (Journal of Smart Agriculture and Environmental Technology, 2023)
The utilization of wetlands as agricultural land requires specific processing techniques, which are relatively expensive and unaffordable for local farmers. The optimization of wetlands as agricultural land by local farmers is usually made by elevating a certain part using the adjacent soil material known as Surjan system. The land management using Surjan system increases the diversity of agricultural products and deals with inundation problems. However, its environmental impact has not been widely studied. The research was conducted by observing the land with Surjan system in Kulonprogo area to determine its characteristics. Interviews with farmers were conducted to determine land management techniques. Soil and gas emissions samples were taken based on the age of the crop. The characteristics of land with Surjan system and conventional rice field were then compared to determine the difference, and the implications of the two agricultural lands on the environment are discussed. Surjan system can increase land productivity, and it can be adopted easily by farmers in other areas with inundation problems. This system is a planting system consisting of mound (the raised beds) and tabukan (the sunken beds that remain inundated). The mound part can be planted with secondary crops, horticulture, and other dryland crops, while the tabukan part can be planted with rice and used for mina padi (rice-fish) farming system. Surjan system provides benefits for environmental management through the prevention of floods and eutrophication, as well as reduction of greenhouse gas emissions in the atmosphere. Land management through Surjan system affects soil pH, redox potential, and organic matter. Land with Surjan system produces lower methane gas emissions than conventional rice fields. It produces methane gas of 4.06 - 45.73 µg / m2 / minute, with soil pH, redox potential, and organic matter of 6.65 - 7.69, (-) 49 - 10 mV, and 1.28 - 3.59%, respectively